The Influence of Health Consciousness, Ecological Motives, and Environmental Knowledge on Purchase Intention Toward Green Cosmetic Products - Shofiyatun Khasanah; Mas Wahyu Wibowo (International Humanities and Applied Science Journal, 2026)
This study examines the influence of health consciousness, ecological motives, and environmental knowledge on purchase intention toward green cosmetic products. The study focuses on consumers residing in Jakarta who demonstrate an intention to purchase environmentally friendly cosmetics A quantitative method was utilized with purposive sampling, leading to 195 valid participants. Data was gathered using a structured survey and subsequently analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) aided by SmartPLS 4.0. The results show that health consciousness, ecological motives, and environmental knowledge all significantly and positively influence purchase intention. These outcomes suggest that both personal health factors and awareness of environmental issues are crucial in determining consumer preferences for eco-friendly cosmetic products. Keywords: Health Consciousness, Ecological Motives, Environmental Knowledge, Purchase Intention